KINETIC 17O EFFECTS IN THE HYDROLOGIC CYCLE: INDIRECT EVIDENCE AND IMPLICATIONS - Angert A.; Cappa C.D.; DePaolo D.J. (My University, 2004)
The abundances of 18O and deuterium in the present and past hydrologic cycle have proven to be an important tool in Earth systems science. In contrast, the abundance of 17O in precipitation has thus far been assumed to carry no additional information to that of 18O. Here, we demonstrate, using known constraints on oxygen isotope abundances from the O2 cycle and existing data about the natural abundance of 17O in water, that the relationship between the discrimination against 17O and 18O in water may vary. This relationship, presented here as θ = ln (17α)/ln (18α), is found to be 0.511 ± 0.005 for kinetic transport effects and 0.526 ± 0.001 for equilibrium effects, with very low temperature sensitivity. As a result, the 17Δ of precipitation is controlled primarily by kinetic effects during evaporation of the initial vapor and, in contrast to the deuterium excess, is independent of the temperature at the evaporation (and condensation) site. This makes 17Δ a unique tracer that complements 18O and deuterium, and may allow for a decoupling of changes in the temperature of the ocean, that serves as the vapor source, from changes in the relative humidity above it. In addition, the 17Δ of ice caps is influenced by the kinetic effects in ice formation, and therefore measurement of ice 17Δ can be used as an additional constraint for better understanding and parameterization of these effects.